Building an import / export business - Weiss, Kenneth D. (Kenneth Duane), 1940- (J. Wiley & Sons, Inc, 2008)
Provides practical guidance and lists further resources for creating an import/export business, covering markets, finance management, shipping procedures, government regulations, and other topics.